Perbandingan Faktor-Faktor yang Mempenagruhi Loyalitas Nasabah pada Perbankan Syariah - Lalu Wibawa Parmadi (EPI 15 UMY 073, 2015)
*73 Perbandingan Faktor-Faktor yang Mempenagruhi Loyalitas Nasabah pada Perbankan Syariah